The Regulators Associated With N6-Methyladenosine in Lung Adenocarcinoma and Lung Squamous Cell Carcinoma Reveal New Clinical and Prognostic Markers - Tan, Shuzhen; Li, Zesong; Li, Kai; Li, Yingqi; Liang, Guosheng; Tang, Zhenye; Kang, Jianhao; Chen, Wenqing; Li, Minhua; Zou, Zhilin; Pi, Guoliang; Zhu, Xiao (Frontiers in Cell and Developmental Biology, 2021)
The aim of this study is to analyze the correlation between the m6A RNA methylation regulators and the occurrence and development of lung cancer. The data of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) were obtained through the TCGA database. Univariate and multivariate Cox regression were used to study the related pathological characteristics. Perl and R 3.5.3 were used throughout the process. We found some of 23 m6A regulators have high expression in lung cancer. In univariate Cox regression, IGF2BP3, HNRNPA2B1, KIAA1429, IGF2BP1, IGF2BP2 and HNRNPC were the risk genes for LUAD, and CBLL1 for LUSC. IGF2BP1 and METTL3 had an impact in pan-cancer. With the help of LASSO Cox regression, we got that 5 genes were chosen for LUAD, 3 for LUSC and 3 for pan-cancer. Finally, the total stage and risk scores of LUAD, the age and risk scores of LUSC, and the T staging and risk score of pan-cancer were important prognostic factors. Our research fully reveals m6A regulators and clinical pathological characteristics in different lung tumors are of great significance for survival and prognosis, laying the foundation for clinical treatment strategy formulation.